All the glimmering stars : a novel [large type] - Sullivan, Mark T. (Center Point Large Print, 2024)
"Anthony Opoka and Florence Okori are coming of age in Uganda in the 1990s. They are both outstanding students and good kids before they are kidnapped and forced into the fanatical Lord's Resistance Army. In a legion of young recruits, no one gets closer than Anthony to powerful messianic warlord Joseph Kony and his darkest secrets. To stay sane as he spirals through chaos, Anthony clings to his childhood lessons about being a good human. Florence's upbringing grounds her, too, helping her keep her dreams alive even as she's pulled deeper into the insanity of Kony's war. At the lowest points of their lives, certain they'll never go home, Anthony and Florence meet by chance, fall in love, and begin to dream of surviving their captivity. They devote their lives to helping their fellow child soldiers escape bondage and return to their families--and redemption--by following the stars." --